Analisis Kinerja Inspektorat Kota Denpasar (Studi Kasus : Evaluasi Laporan Akuntabilitas Kinerja Pemerintah (LAKIP) Inspektorat Kota Denpasar Tahun 2015/2016) - Dwi Apsari, A. A Istri Agung (CITIZEN CHARTER, 2018)
ABSTARCT The Government Agency's Performance Accountability System (SAKIP) is one of the government's efforts to improve the government's responsibilities and performance. Inspectorate Denpasar is one of them, which is very instrumental in the implementation of SAKIP in Denpasar City. However, in practice there are many performance targets that can’t be fulfilled to realize effective SAKIP in Denpasar City area. The purpose of this study is to find out how the performance of the Inspectorate of Denpasar evaluated from the Government Accountability Performance Accountability Report (LAKIP) Inspectorate Denpasar in 2015/2016. This is evident from the evaluation of LAKIP that shows the ability of Inspectorate that succeed in preventing deviation in Denpasar City area. However, it hasn’t succeeded in increasing the accountability value of Denpasar City. Inspectorate of Denpasar City also need to establish cooperation and increase assertiveness at Organization of Regional Devices in Denpasar City in launching process of implementation of supervision. Keywords: Performance Accountability System of Government Institution, Local Government Performance, Accountability